PENGARUH BUDAYA ORGANISASI DAN KOMITMEN ORGANISASI TERHADAP KINERJA KARYAWAN MELALUI ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) SEBAGAI VARIABEL INTERVENING (Studi Kasus pada Karyawan PT Masscom Graphy Semarang) - Venty Hertina Maulani; Widiartanto Widiartanto; Reni Shinta Dewi (Universitas Diponegoro, 2015)
Employee performance is one of the benchmarks in the business of a company to achieve its objectives. Employees play a role in carrying out various operations of the company which will affect the company's success in achieving its objectives. Organizational culture and organizational commitment has a role in improving the performance of employees. Moreover, Organizational Citizenship Behavior (OCB) is one of the factors of employee performance. Therefore, three things need to be considered in improving employee performance by PT Masscom Graphy Semarang. Type of this research is Explanatory Research. Samples are 127 respondents. Samples were taken using proportional random sampling technique. Data were analyzed qualitatively and quantitatively using a data collection instrument (questionnaire) was previously tested through validity and reliability test. Analyzing of data’s result using analysis of data tables, simple linear regression analysis, multiple linear regression analysis, t-test, F-test, path analysis, and Sobel test. The results indicated that organizational culture and organizational commitment either partially or simultaneously significant on Organizational Citizenship Behavior (OCB) and Employee Performance. Based on calculations from sobel test and path analysis showed that Organizational Citizenship Behavior (OCB) mediating organizational culture and organizational commitment to employee performance.